Ciphertext policy attribute-based encryption with hierarchical domain authorities and users in cloud. (2017) - Wei, Jing; Zhang, Leyou
Attribute-based encryption (ABE) can propose the fine-grained access control policy for encrypted data in cloud. The characteristics of the attributes in the existing works are treated as same level but in the real life the attributes and domain authorities are always in the different levels. It produces additional computation costs and storage costs for users. To overcome these shortcomings, a new ABE scheme is proposed in this paper. The proposed scheme combines the ciphertext-policy attribute-based encryption (CP-ABE) scheme with hierarchical identity-based encryption (HIBE) which issues a ciphertext-policy hierarchical attribute-based encryption (CP-HABE). Both the main domain authorisations and users achieve hierarchical encryption under the fine-grained access control. In addition, the proposed scheme inherits flexibility and achieves scalability with short ciphertexts. Under three static assumptions instead of other strong assumptions, it also achieves full security in the standard model.